Spectrophotometric Studying for Some Organic Compounds as (Drugs) by using (FT.I.R.) Spectrum and High Performance Liquid Chromatographic Technic for Valsartan and Hydrochlorothiazide in Pharmaceutical Preparations Tablets - Imad Tarek Hanoon (Journal of Global Pharma Technology, 2016)
Used and complete organic analytical spectrum by using (FT.I.R.) spectrum to prove the chemical structures for some organic compounds as (drugs) of Valsartan and Hydrochlorothiazide (1) and supported by reverse phase high performance liquid chromatography (HPLC) method has been developed for the determination of valsartan and hydrochlorothiazide in pharmaceutical preparations tablets .Chromatography was carried out on supelco L7 column (25cm×4.6m.m), 5µm. Using Buffer solution , methanol and acetonitrile at ratio 35 :25 :40 accurately as mobile phase. The flow rate was 1.0 ml.min-1 with Uv-detection at 270 nm at 50C°. Separation was completed within 1.42 min and 5.74 min. Calibration curve was linear coefficient correlation 0.9948 and 0.9980 over a concentration range of (30-50µg.ml-1) and (5-15µg.ml-1). The relative standard deviation (RSD) was found <1%.The proposed method was successfully applied to the determination of valsartan and hydrochlorothiazide in pharmaceutical preparations.Keywords: Valsartan, Hydrochlorothiazide, Linearity, FT.I.R., HPLC, Tablet form